Verhulst equation


by asdf1
Tags: equation, verhulst
asdf1
asdf1 is offline
#1
Oct16-05, 03:26 AM
P: 741
for the following question:
y`-Ay=-By^2

my problem:
Suppose u=y^(-1)
so u`=-y^(-2)y`=B-Au
so du/(B-Au)= dx
=> B-Au=ce^x
=> u=(B-ce^x)/A
so y=1/u=a/(B-ce^x)

however, the correct answer should be y=1/[(B/A)+ce^(-ax)]
does anybody know where my calculations went wrong?
Phys.Org News Partner Science news on Phys.org
Review: With Galaxy S5, Samsung proves less can be more
Making graphene in your kitchen
Study casts doubt on climate benefit of biofuels from corn residue
hotvette
hotvette is offline
#2
Oct17-05, 12:17 AM
HW Helper
P: 930
Quote Quote by asdf1
so u`=-y^(-2)y`=B-Au
Take a look at this step again. I think one of the terms has the wrong sign.
asdf1
asdf1 is offline
#3
Oct17-05, 06:20 AM
P: 741
i see~
thanks!!!


Register to reply

Related Discussions
Solving a partial differential equation (Helmholtz equation) Differential Equations 7
Deriving the continuity equation from the Dirac equation (Relativistic Quantum) Advanced Physics Homework 3
[SOLVED] Lenses - Thin-Lens Equation and Magnification Equation Introductory Physics Homework 2
Why is Euler equation similar to the gradient of Hamilton-Jacobi equation? General Physics 1
Why is Euler equation similar to the gradient of Hamilton-Jacobi equation? General Physics 1